Giant cystic lymphangioma of the mesentery: varied clinical presentation of 3 cases - Rami, Mohamed (The African Field Epidemiology Network, 2012)
Giant cystic lymphangioma is an uncommon mesenteric tumor which is usually reported in children. In this paper, we describe 3 cases, that was admitted in our department, two with abdominal distension, pain, and an abdominopelvic mass; the other present an acute abdomen. Preoperative studies including abdominal ultrasonography and computed tomography failed to determine the cause of the pain for the female patients. The laparotomy found a giant cystic tumor of the small bowel mesentery. The histological study showed a tumor that was diagnosed as a cystic lymphangioma. Based on those three cases a review of the literature is suggested.